2007
DOI: 10.1002/jcb.21399
|View full text |Cite
|
Sign up to set email alerts
|

Pristimerin induces apoptosis by targeting the proteasome in prostate cancer cells

Abstract: Pristimerin is a natural product derived from the Celastraceae and Hippocrateaceae families that were used as folk medicines for anti inflammation in ancient times. Although it has been shown that pristimerin induces apoptosis in breast cancer cells, the involved mechanism of action is unknown. The purpose of the current study is to investigate the primary target of pristimerin in human cancer cells, using prostate cancer cells as a working model. Nucleophilic susceptibility and in silico docking studies show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 36 publications
4
97
0
1
Order By: Relevance
“…Furthermore, we found that treatment with pristimerin inhibited the migration and invasion of MDA-MB-231 cells in vitro in a dose-dependent manner and the growth and invasion of implanted breast tumors in vivo. These novel data extend previous findings (Wu et al, 2005;Yang et al, 2008;Tiedemann et al, 2009) and suggest that pristimerin may have broad antitumor activity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, we found that treatment with pristimerin inhibited the migration and invasion of MDA-MB-231 cells in vitro in a dose-dependent manner and the growth and invasion of implanted breast tumors in vivo. These novel data extend previous findings (Wu et al, 2005;Yang et al, 2008;Tiedemann et al, 2009) and suggest that pristimerin may have broad antitumor activity.…”
Section: Discussionsupporting
confidence: 90%
“…The redundant metastatic signals by different activated GPCRs simultaneously drive the migration of breast cancer cells, which makes the inhibition of breast cancer metastasis by a GPCR-specific inhibitor unfeasible. Ideally, simultaneous 1 can inhibit tumor cell proliferation by inhibiting the NF-κB pathway and cell cycling (Boire et al, 2005;Costa et al, 2008;Yang et al, 2008;Byun et al, 2009;Tiedemann et al, 2009). In addition, prestimerin has been reported to induce caspase-dependent apoptosis of breast cancer cells (Wu et al, 2005) and prostate cancer cells in vitro (Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IC 50 value for the inhibition of purified rabbit 20S proteasome with pristimerin was 2.2 μM. Similarly, pristimerin also potently inhibited 26S proteasome chymotrypsin-like activity in a extract prepared from exponentially grown PC-3 cells, with an IC 50 of 3.0 μM (Yang, Landis-Piwowar et al, 2008). About 40% inhibition of cellular proteasome activity occurred in C4-2B cells with 5 μM of pristimerin and was accompanied by AR suppression with consequent apoptosis induction.…”
Section: Fig 7 Pentacyclic Triterpenoidsmentioning
confidence: 88%
“…Pristimerin targets the proteasome to induce apoptosis in human PC-3 and AR-positive C4-2B cells (Yang, LandisPiwowar et al, 2008). Proliferation of PC-3 cells was inhibited by pristimerin (Chang et al, 2003) with induction of apoptosis that correlated with inhibition proteasome activity (Yang, Landis-Piwowar et al, 2008). The IC 50 value for the inhibition of purified rabbit 20S proteasome with pristimerin was 2.2 μM.…”
Section: Fig 7 Pentacyclic Triterpenoidsmentioning
confidence: 92%